THE EFFECT OF CARD CHALLENGE GAMES ON MOTHER'S KNOWLEDGE ABOUT STUNTING - Anggraini, Ika Rizki; Fitriyani, Novia; Susanti, Henny Dwi; Setyowati, Lilis (Jurnal Keperawatan, 2025)
Introduction: Stunting in Indonesia is a serious health problem, with a prevalence of 24.1%. This condition risks threatening the quality of life of the nation's next generation due to linear growth disorders caused by malnutrition and inadequate nutritional intake. One of the main causes of high stunting rates is the lack of maternal knowledge about stunting itself. Therefore, increasing mothers' knowledge about stunting is very necessary, and one of the effective methods is to use visual-based educational media. Objectives: This study aims to analyze the effect of card challenge, a visual-based educational media, on increasing maternal knowledge about stunting. Methods: This study uses a quasi-experimental design with a one group pre-post test design method. The sample used in this study is 50 mothers who have toddlers. Before and after the intervention in the form of card challenge, mothers' knowledge of stunting was measured and analyzed using the Wilcoxon Signed Rank Test statistical test to assess significant changes. Results: The results showed that there was a significant increase in maternal knowledge after being given a card challenge game with a value of p = 0.000 (p < 0.05). This indicates that the intervention using card challenge games has succeeded in significantly increasing mothers' understanding of stunting. Conclusions: Card challenge games have proven to be effective in increasing mothers' knowledge about stunting, providing a positive impact on stunting prevention efforts. This study emphasizes the importance of a creative approach in health education that can be accepted and applied by the wider community, especially for mothers with toddlers. This intervention is expected to be a broader model in accelerating the reduction of stunting rates in Indonesia.